2022
DOI: 10.3892/ijmm.2022.5153
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA protects against chronic obstructive pulmonary disease via exosome‑shuttled miR‑486‑5p

Abstract: Chronic obstructive pulmonary disease (COPD) is one of the major causes of death worldwide today, and its related morbidity has been predicted to show an increase in subsequent years. Recent studies have shown that Danshen, a Chinese herbal medicine, is a potential drug in the treatment of inflammation-related lung diseases. COPD was induced in this study using cigarette smoke (CS) exposure plus intranasal inhalation of lipopolysaccharide to ascertain whether the main pharmacological component from Danshen, ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
(49 reference statements)
0
2
0
Order By: Relevance
“… 2020 ; Tian et al. 2022 ). Of note, STS could also reverse chemotherapeutic drug-induced neuropathic pain and attenuate the malignancy of glioma cells (Di Cesare Mannelli et al.…”
Section: Discussionmentioning
confidence: 99%
“… 2020 ; Tian et al. 2022 ). Of note, STS could also reverse chemotherapeutic drug-induced neuropathic pain and attenuate the malignancy of glioma cells (Di Cesare Mannelli et al.…”
Section: Discussionmentioning
confidence: 99%
“…Up to date, sorafenib is also recommended as the first-line treatment for patients with advanced HCC. However, more and more evidences suggest HCC or stroma-cells derived exosomes may induce drug resistance and many patients develop resistance after months of treatment ( Tian D et al, 2022 ). It has been shown that exosomes from HCC cells could induce sorafenib resistance through activating the HGF/c-Met/Akt signaling pathway and inhibiting sorafenib-induced apoptosis ( Qu et al, 2016 ).…”
Section: Exosomes In Cancer Therapymentioning
confidence: 99%